1993
DOI: 10.1063/1.858688
|View full text |Cite
|
Sign up to set email alerts
|

Vortex shedding from long slender cylinders in near-axial flow

Abstract: It has been found that vortex shedding can occur from long cylinders at small angles of yaw, i.e. in near-axial flow. The range of Reynolds number over which this can take place has been determined for yaw angles between 0° and 10°. Results for vortex-shedding frequencies are also presented, and compared with existing data for larger yaw angles. It is suggested that the phenomenon may be relevant to turbulence-generation mechanisms in thick axisymmetric turbulent boundary layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Such separation can be expected to have a particularly strong effect on the flow physics. For instance, Bull and Dekkers 14 found that for very long cylinders (L/Dϳ3000) with correspondingly very thick boundary layers, organized vortex shedding occurred down to yaw angles as little as ␣ϭ1°over a limited range of Re D . The effect of the inflow boundary layer thickness as well as the limits of the organized vortex shedding and trailing vortex regimes in the ␣ -Re D plane are not well understood.…”
Section: Introductionmentioning
confidence: 98%
“…Such separation can be expected to have a particularly strong effect on the flow physics. For instance, Bull and Dekkers 14 found that for very long cylinders (L/Dϳ3000) with correspondingly very thick boundary layers, organized vortex shedding occurred down to yaw angles as little as ␣ϭ1°over a limited range of Re D . The effect of the inflow boundary layer thickness as well as the limits of the organized vortex shedding and trailing vortex regimes in the ␣ -Re D plane are not well understood.…”
Section: Introductionmentioning
confidence: 98%
“…Unsteady tugging motion by the towing system and lift from steering birds that try to maintain the streamer at a constant depth also add to the complexity of the flow environment. Experiments by Bull and Dekkers (1993), Heenan and Morrison (2002a,b) and Snarski (2004) indicate that the flow characteristics in the turbulent boundary layer surrounding long cylindrical objects like seismic streamers will change when the local angle between the streamer and the flow direction exceeds 6-15…”
Section: Weather Noise Generationmentioning
confidence: 99%
“…Cross flow can also be induced by ocean currents. Experiments by Bull and Dekkers (1993), Morrison (2002a,b), andSnarski (2004) indicate that the flow characteristics in the turbulent boundary layer surrounding long cylindrical objects like seismic streamer cables will change when the local angle between the streamer and the flow direction exceeds approximately 6…”
Section: Swell Noisementioning
confidence: 99%
See 2 more Smart Citations